PRODUCT COMPETITIVENESS DEVELOPMENT THROUGH MODULATION-BASED INNOVATION AND REDUCTION OF EFFORTS - Mentari Clara Dewanti; Daisy Martina Rosyanti; Fani Khoirotunnisa (BBM (Buletin Bisnis & Manajemen), 2023)
Competition in an increasingly competitive business  is one of the  threats for every entrepreneur, they are required to be able to maintain and increase product sales in the midst of this competition, so efforts are needed to improve and change the products produced for the better and have competitiveness. The necessary effort is to innovate which aims to maintain and increase product sales volume. Innovation can be done based on modulation that involves changing the basic characteristics of the product through the increase or decrease of those characteristics. In addition, it can use innovation-based reduction efforts that do not change the product, but through changes to the increase in size on the market. The purpose of this study is to determine the role of modulation-based innovation and reducing efforts in developing product competitiveness in the Pia Latief Home Industry. This research is  a field research and uses a qualitative approach. In data analysis, it includes data reduction, data presentation (display data), and conclusion drawing or verification. The results of this study show that innovation plays a role in developing product competitiveness as evidenced by an increase in sales volume as evidenced by an increase in sales starting in 2018-2021. The increase is due to modulation-based and effort-based product innovation.